Does Concomitant Use of Methotrexate with JAK Inhibition Confer Benefit for Cardiovascular Outcomes? A Commentary - Taylor, Peter C; Balsa, Alejandro; Mongey, Anne-Barbara; Filková, Mária; Chebbah, Myriam; Le Clanche, Solenn; Verhagen, Linda A W; Witte, Torsten; Opris-Belinski, Daniela; Marotte, Hubert; Avouac, Jérôme (Rheumatology and therapy, 2024)
This commentary explores the potential cardiovascular (CV) benefits of combining methotrexate (MTX) and Janus kinase inhibitors (JAKis) in the treatment of rheumatoid arthritis (RA). While European guidelines recommend MTX as first-line treatment, concerns about the CV risks associated with JAKis have emerged. This article reviews the existing literature to assess the role of concomitant MTX in reducing CV risk when used with JAKis. Clinical trials confirm the efficacy of JAKis in combination with MTX in terms of treatment outcomes in RA. However, the number of major adverse cardiovascular events (MACEs) reported is too low to draw conclusions on adverse CV outcomes. Indirect evidence does, however, suggest potential protective effects of MTX on CV outcomes, as several mechanisms may contribute to MTX's cardioprotective effects, including reduced inflammation, adenosine monophosphate-activated protein kinase (AMPK) activation, increased cholesterol efflux, and adenosine accumulation. These mechanisms and the available data may support the case for CV benefits of concomitant MTX when JAKis are used in the treatment of patients with RA, although further research is needed. In particular, the lipid paradox associated with RA highlights the complex relationship between RA treatments (MTX, JAKis, tumor necrosis factor (TNF) inhibitors, and interleukin (IL)-6 receptor inhibitors), inflammation, different lipid profiles, and CV risk. In the absence of contraindications and when MTX is tolerated, this commentary suggests the concomitant use of MTX and JAKis as a preferred option for optimizing CV protection in patients with RA.
Keywords: Combination therapy; Methotrexate; Janus kinase inhibitors; Rheumatoid arthritis; Cardiovascular